PLGA microspheres and nanoparticles drug delivery for ocular diseases - Tan, Chun Yi. (2010)
The use of biodegradable polymer microspheres and nanoparticles in topical form or for injection to the eye for treatment of ocular diseases such as glaucoma and age related macular degeneration is increasingly popular. One of the drugs used is Latanoprost for the treatment of glaucoma.